2019
DOI: 10.1371/journal.pone.0226001
|View full text |Cite
|
Sign up to set email alerts
|

In vivo ultrasound thermal ablation control using echo decorrelation imaging in rabbit liver and VX2 tumor

Abstract: The utility of echo decorrelation imaging feedback for real-time control of in vivo ultrasound thermal ablation was assessed in rabbit liver with VX2 tumor. High-intensity focused ultrasound (HIFU) and unfocused (bulk) ablation were performed using 5 MHz linear image-ablate arrays. Treatments comprised up to nine lower-power sonications, followed by up to nine higher-power sonications, ceasing when the average cumulative echo decorrelation within a control region of interest exceeded a predefined threshold (− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The results showed that AUROC values of ablated area predicted by echo decorrelation imaging were >.8 in liver tissue and >.7 in tumor tissue. Abbass et al [84][85][86] investigated the strategy of real-time control and feedback of HIFU and bulk ultrasound ablation of bovine liver in vitro and rabbit liver with VX2 tumor in vivo using echo decorrelation imaging. The closed-loop control condition of ablation was that the minimum-decorrelation (Min dec ) or average-decorrelation (Ave dec ) in the selected region of interest (ROI) exceeded control thresholds.…”
Section: Ultrasonic Echo Decorrelation Imagingmentioning
confidence: 99%
“…The results showed that AUROC values of ablated area predicted by echo decorrelation imaging were >.8 in liver tissue and >.7 in tumor tissue. Abbass et al [84][85][86] investigated the strategy of real-time control and feedback of HIFU and bulk ultrasound ablation of bovine liver in vitro and rabbit liver with VX2 tumor in vivo using echo decorrelation imaging. The closed-loop control condition of ablation was that the minimum-decorrelation (Min dec ) or average-decorrelation (Ave dec ) in the selected region of interest (ROI) exceeded control thresholds.…”
Section: Ultrasonic Echo Decorrelation Imagingmentioning
confidence: 99%
“…14 To transmit enough laser energy to the deep-buried tumors through malignant tissues deeper than 10 cm, operative exposure is a common option, which has the problem of large damage. 15 Optical fibers, which are small (few hundred micrometers in diameter), flexible, nontoxic, and chemically inert, have already proven to be valuable for in vivo clinical applications such as endoscopic procedures, illumination light guides, and laser power transmission for surgical applications. 16 Hence, we hypothesize that optical fibers could be inserted into the deep-buried tumors to transmit NIR-II laser energy to deeped buried tumors for in situ NIR-II photothermal therapy.…”
Section: Introductionmentioning
confidence: 99%